Key Components of Healthy Soils and Their Role in Crop Production - C. J. Hsiao; Gretchen Sassenrath; Charles Rice; L. Zeglin; G. Hettiarachchi (Kansas Agricultural Experiment Station Research Reports, 2017)
Soil health is a confusing term that means different things to different people. To a crop producer, healthy soils are critical for good crop growth and yield. Some soil properties include soil texture, such as the relative percentage of sand, silt and clay; the water content; nutrient levels; organic carbon content; the microbial community; and microbial activity. These properties are determinants of soil health. Our research confirmed that changes in soil management affect the composition and activity of soil microorganisms in surface soils. Greater concentrations of microbial biomass and arbuscular mycorrhizal fungus (AMF) in the no-till agricultural system indicated healthier soils in this system. Our research also indicated microbial properties in subsurface soils were determined by parent materials and weathering.
Keywords: crop production; soil health; soil microbiology; phospholipid fatty acid analysis; soil enzyme activity analysis